2018
DOI: 10.1111/apt.14991
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety after coeliac disease diagnosis predicts mucosal healing: a population‐based study

Abstract: Summary Background Coeliac disease has been linked to anxiety and depression. However, their association with mucosal healing is unknown. Aim To examine the relationship between anxiety, depression and mucosal healing in coeliac disease. Methods Between 1969 and 2008, we collected data on all small intestinal biopsies with villous atrophy from Sweden's 28 pathology departments. We restricted our cohort to individuals with data on follow‐up biopsy (either persistent villous atrophy [n = 3317] or mucosal healing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 53 publications
4
44
0
Order By: Relevance
“…Adherence and self-advocacy are particularly problematic for adolescents as they venture outside of the home and become more independent (13,14) . The focus on food and eating behaviours, and possibly even adherence to a GFD, may be associated with an increased risk of psychosocial problems and disordered eating patterns and behaviours in adolescents with CD (15)(16)(17)(18)(19)(20)(21) .…”
Section: Introductionmentioning
confidence: 99%
“…Adherence and self-advocacy are particularly problematic for adolescents as they venture outside of the home and become more independent (13,14) . The focus on food and eating behaviours, and possibly even adherence to a GFD, may be associated with an increased risk of psychosocial problems and disordered eating patterns and behaviours in adolescents with CD (15)(16)(17)(18)(19)(20)(21) .…”
Section: Introductionmentioning
confidence: 99%
“…
EDITORS,We read with interest the recent study by Ludvigsson et al 1 Authors performed a nationwide population-based cohort study in patients diagnosed with coeliac disease (CD) between 1969 and 2008. 1 The authors stated that anxiety and depression are more common in coeliac disease patients with mucosal healing, both before and after follow-up biopsy. After reviewing the research, we have several concerns about the design and results of the study.In this study authors performed regression analysis to evaluate the impact of various factors on anxiety and depression including age at follow-up biopsy, gender, duration of coeliac disease at the time of follow-up biopsy, calendar period of first biopsy and educational attainment.
…”
mentioning
confidence: 99%
“…However, while maintaining a GFD is ideal for disease management, it is also recognised to be challenging both practically and emotionally . The study conducted by Ludvigsson et al provides a valuable exploration of the relationship between psychological comorbidity and mucosal healing associated with maintaining a GFD.…”
mentioning
confidence: 99%
“…In a nationwide longitudinal population‐based cohort study involving 7648 individuals, Ludvigsson et al explored the association between diagnosis of anxiety or depression and its relationship to mucosal healing. The authors found that the risk of developing anxiety was 2.8 per 1000 person‐years of follow‐up in the mucosal healing group (n = 4331) vs 2.1 per 1000 in the group identified with persistent villous atrophy (n = 3317).…”
mentioning
confidence: 99%
See 1 more Smart Citation